A Stylistic analysis of Coke Studio’s selected English Songs - Ahmad, Ayaz; Ali, Arslan; Maryam (JELLL, 2023)
Language is a very basic element to convey human expressions, thoughts, and emotions. Through the medium of language human beings interpret everything around them; songs are an example of language. To make the songs sound appealing to the listeners, singers may deviate from the lyrics as they sing. The focus of this study is on the semantic deviation to find out the style of the writer and to find the meaning. For this purpose, researcher chooses two English songs from Coke Studio, “I’m in Love”, and “My Happiness”. This study presents lexical parallelism, and morphological parallelism, and at the end describes the Semantic deviation. For this study stylistics is the most suitable approach, stylistics is a field of linguistics that examines the relationship between language and its artistic use in literature, music, advertisements, and other forms of expression. This study uses the semantic level, lexical level, and morphological level of stylistics for this research. The researcher used the qualitative method and content analysis for this study, and applies the stylistic analysis on the selected songs of Coke Studio. This study finds the semantic, lexical, and morphological terms from the song’s lyrics. This study also classified the terms that find in the Songs and also interpreted the meaning in terms of stylistics. This study finds out, in both songs writers used the same semantic, lexical, and morphological devices. The most occurring device in both songs is Semantic Parallelism; the interpretation of stylistic devices suggests that the theme of love is mostly explored in the song.